MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN METODE GROUP INVESTIGATION ILMU PENGETAHUAN ALAM DAN SOSIAL KELAS IV - Khoirul Huda; Binti Khoiriyah; Pixyoriza (STKIP Subang, 2026)
The low science learning outcomes for class IV UPTD SD Negeri 1 Tambah Subur students are caused by less interesting learning so that student learning outcomes are less than optimal. This research aims to improve learning outcomes through the application of the Group Investigation (GI) method to material on Natural Wealth in My Region. The research used a Classroom Action Research (PTK) design which was carried out in two cycles, each through planning, implementation, observation and reflection stages. The research subjects were 26 class IV students. Data was collected through observation, interviews, documentation, and learning outcomes tests, then analyzed using mixed methods (qualitative and quantitative). The research results showed a significant improvement: the percentage of learning completion increased from 62% in cycle I to 84% in cycle II, resulting in a 22% increase. Thus, the use of the Group Investigation (GI) method has been proven to significantly improve the science learning outcomes of class IV UPTD students at SD Negeri 1 Tambah Subur.